A retrospective, observational study of supine percutaneous nephrolithotomy. (July 2018) - Srinivas, SU; Gall, Z; Lynch, N; Pollard, A; Counsell, A; Brown, S; Adeyoju, AAB
Objective: The objective of this study is to assess stone clearance and perioperative complication rates of supine percutaneous nephrolithotomy (PCNL). Methods: This was a retrospective, observational study of supine PCNL performed in a surgical unit at a district general hospital by two surgeons in the United Kingdom. Data collected included patient demographics, comorbidities, complexity of renal calculi, perioperative complications and stone clearance rates. Results: A total of 112 supine PCNL procedures were observed in this study. The mean (SD) American Society of Anesthesiologists (ASA) grade and Guy's Stone Score were 2.0 (0.75) and 2.3 (1.06) respectively. The median (interquartile range (IQR)) duration of in-patient admission was four (one) nights. Complete stone clearance was achieved in 74 (67.3%) of the procedures, while more than 90% clearance of the renal stone burden was achieved in a further eight (7.3%). The most common perioperative complications recorded were blood loss requiring blood transfusion (three (2.7%)) and postoperative fever (two (1.8%)). Conclusion: This case series shows that supine PCNL can lead to good stone clearance and low complication rates.